Kajian Teknis Pengaruh Variabel Shaking Table Terhadap Peningkatan Kadar dan Recovery Pencucian Bijih Timah Unit di Unit Metalurgi PT Timah Tbk - Novrida Siregar; Janiar Pitulima; Haslen Oktarianty (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2022)
The Mineral Processing Sector (BPM) is a place for processing precious tin minerals with other associated minerals. This research was conducted because the tin content in table water as feed in processing is still quite economical, namely 9.64% Sn and the minimum level that must be achieved as smelting feed is >60% Sn. The data collection method was carried out by conducting feed analysis with the GCA test to determine the levels and distribution of minerals in the feed. Furthermore, the shake table tool variations are adjusted such as stroke lengths of 15 mm, 22 mm, 10 mm with a sample result of 9 samples and the speed of air flow over the table is carried out as many as 3 variations, namely 0.025 m/s, 0.011 m/s, 0.014 m/s with results of 9 samples. Then the combination of the two variables was carried out with the results of 27 samples. The results of the GCA analysis were carried out to see the effect on levels and recovery. The results of the combination of stroke length and water flow velocity were the most optimal in combination with a stroke length of 15 mm and a water flow velocity of 0.025 m/s resulting in a concentrate of 58.44% Sn, moderately 6.26% Sn, and tailings 2.72% Sn as well as recovery. by 58.49%.